A small open economy DSGE model with workers' remittances. Issue 6 (4th May 2020) - Rehman, Muhammad; Khan, Sajawal; Hayat, Zafar; Balli, Faruk
Abstract : Purpose: In this paper, the authors develop and estimate a small open economy dynamic stochastic general equilibrium (DSGE) model with an enriched micro-founded specification to account for foreign remittances, an important source that helps bridge the trade gap in many developing and emerging market economies. Design/methodology/approach: Although the authors' specification provides a general frame for the analysis of the role of workers' remittances, they motivate and calibrate the model with specific focus on Pakistan, where most of the trade deficit is met through the remittance channel. Findings: The results indicate that a negative shock to workers' remittances hampers real growth via decreased consumption and imported investment goods, while it builds pressure on exchange rate and hence worsens current account balance. These results indicate that too much dependence on workers' remittances to help meet foreign exchange deficits may potentially leave the economy in doldrums in case sizable negative shocks occur to the flow of foreign remittances. Originality/value: The authors develop and estimate a small open economy DSGE model with an enriched micro-founded specification to account for foreign remittances, an important source that helps bridge the trade gap in many developing and emerging market economies.